Determinan Efisiensi Perbankan BPR Syariah Indonesia - Isnan Murdiansyah (Akuntabilitas, 2021)
This research aims to determine how the level of efficiency is measured by the DEA method and what the inhibiting factors are, how the variables of the level of profitability, level of complexity, level of health, capital ownership can affect the level of efficiency and its relationship with CAMEL. The research is located in the province of East Java with a total sample of 77 samples. The analysis technique used is tobit regression and Spearman correlation. The results showed that the level of efficiency of BPR Syariah in East Java was very fluctuating and the management of the input variables had not yet reached the maximum level when compared to the output variables which were the results of the management of these input variables. The results of the Spearman correlation test show that the level of efficiency is related to CAMEL because in CAMEL there is also an efficiency component even though the weighting value is small. Overall, it can be concluded that the level of perfect efficiency can be achieved not only by comparing the input and output variables optimally but also considering other factors outside of these variables.